2007
DOI: 10.1111/j.1471-1842.2007.00726.x
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional/multiprofessional health professions education: designing an efficient search to scope the literature of this exploding field

Abstract: Background and objective : With the advent of an interprofessional approach to delivering health care in today's health care systems, should health care professionals be educated together? Supported by policy-making circles worldwide, interprofessional education is accumulating a research literature at an exponential rate. Using one-word search terms in the medline query box for scoping this body of literature, we obtained an unmanageable number of articles (342 338 in all fields). The objective of our study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Classification and retrieval of studies could pose a concern when it comes to searching. Nevertheless, Ioannis and Dimoliatis (2007), has demonstrated that the number of studies in this field is exploding. The authors demonstrate that in the databases the prefix "inter*" occurs if included in the algorithm is a better than the "multi*" predictor of the number of citations that will be retrieved, especially if it is included in the title alone.…”
Section: Limitationsmentioning
confidence: 99%
“…Classification and retrieval of studies could pose a concern when it comes to searching. Nevertheless, Ioannis and Dimoliatis (2007), has demonstrated that the number of studies in this field is exploding. The authors demonstrate that in the databases the prefix "inter*" occurs if included in the algorithm is a better than the "multi*" predictor of the number of citations that will be retrieved, especially if it is included in the title alone.…”
Section: Limitationsmentioning
confidence: 99%
“…This proposition makes sense given that scholars have used vague concepts and terms to refer to multiple types of interactions in health care (Barr, ). Furthermore, adopting more specific terms to refer to different types of interactions in health care would make it easier to identify relevant literature and to design policies and educational programmes that address a given problem (Dimoliatis & Roff, ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This could lead to policies and educational interventions that target more achievable forms of teamwork. It would also make it easier for researchers to find literature that is relevant to the type of interaction that they are interested in (Dimoliatis & Roff, ).…”
Section: Implications For Practicementioning
confidence: 99%
“…According to numerous studies, the first important step in implementing IPCP (in full?) within a healthcare organization is to provide "Patient centered care", which means to provide care in an environment that gives patients high quality care according to his/ her needs [7,8]. Due to its considerable importance in the health sector, Interprofessional collaboration is starting to be taught to healthcare students under the name of inter-professional education (IPE).…”
Section: Introductionmentioning
confidence: 99%